2013
DOI: 10.1371/journal.pone.0075463
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase 1 Identifies Cells with Cancer Stem Cell-Like Properties in a Human Renal Cell Carcinoma Cell Line

Abstract: Cancer stem cells (CSC) or cancer stem cell-like cells (CSC-LCs) have been identified in many malignant tumors. CSCs are proposed to be related with drug resistance, tumor recurrence, and metastasis and are considered as a new target for cancer treatment; however, there are only a few reports on CSCs or CSC-LCs in renal cell carcinoma (RCC). Different approaches have been reported for CSC identification, but there are no universal markers for CSC. We used two different approaches, the traditional side populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 50 publications
2
88
0
Order By: Relevance
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the sorting methods of CSCs include flow cytometry based on special cell surface markers, the side population cell sorting technique, tumor sphere culturing and the ALDEFLUOR™ assay (6)(7)(8)(9). Previous studies have identified the CSCs from colon, breast and glioblastoma cancer, as well as other cancer cell lines, using the sphere culturing method (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-SP RCC cells, the SP is distinguishable by increased sphere-forming ability in vitro , enhanced proliferative potential, and greater expression levels of β-catenin, Sonic Hedgehog, Notch, and Pax-2 stem cell markers. Furthermore, the SP had an abundance of ALDH-positive cells, suggesting that ALDH enzymatic activity may be associated with the SP (Ueda et al, 2013). DNAJB8 knockout cells displayed a decreased ratio of SP to non-SP cells and reduced sphere-forming ability, indicating that DNAJB8 contributes to CSC-like phenotype of RCC (Nishizawa et al, 2012).…”
Section: Intracellular Markers In Renal Cscsmentioning
confidence: 99%
“…Importantly, in the metastatic RCC cell lines, ALDH high cells formed about 15% of the total number of cells and had higher sphere-forming capacity, self-renewal ability, and tumorigenicity than ALDH low cells. While anther study showed that ALDH gene expression was correlated with tumor grade but not with tumor stage in patients with RCC (16). Overall pooled analysis suggested that high CSCs markers, including CD133, CD44, CXCR4 and CD105, expression predicted poor overall survival, cancer-specific survival, disease-free survival and progression-free survival (17).…”
Section: Introductionmentioning
confidence: 99%